2021
DOI: 10.9734/ajeba/2021/v21i130340
|View full text |Cite
|
Sign up to set email alerts
|

Good Working Environment and Work Performance Across Higher Institutions in Buea

Abstract: The objective of this study was to examine how good working environment on work performance of teachers across private higher institutions in Buea. The sample size included a total of one hundred and seven (107) teachers drawn from one hundred and eighty seven (187) teaching staff of the selected institutions. Nine (9) schools were first selected purposely base on their staff strength. Then four schools were further selected using the simple probability random sampling technique. Respondents were then selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The third function of Human Resource Management (HRM) that is implemented at Higher Education Institutions (HEIs) pertains to the rewards and compensation offered to the employees. Based on prior research in the field of Human Resource Management (HRM), rewards and compensation typically manifest in various forms, including but not limited to monetary remuneration, moral incentives, and recognition for exceptional achievement (Lious, Oliveira, & Pimentel, 2021). In order to optimise the efficacy of incentive and compensation systems, academic institutions establish a connection between rewards and the last stage of human resource management (HRM), known as performance appraisal.…”
Section: Impact Of Covid-19 On Hrm Practices In Higher Educationmentioning
confidence: 99%
“…The third function of Human Resource Management (HRM) that is implemented at Higher Education Institutions (HEIs) pertains to the rewards and compensation offered to the employees. Based on prior research in the field of Human Resource Management (HRM), rewards and compensation typically manifest in various forms, including but not limited to monetary remuneration, moral incentives, and recognition for exceptional achievement (Lious, Oliveira, & Pimentel, 2021). In order to optimise the efficacy of incentive and compensation systems, academic institutions establish a connection between rewards and the last stage of human resource management (HRM), known as performance appraisal.…”
Section: Impact Of Covid-19 On Hrm Practices In Higher Educationmentioning
confidence: 99%
“…The findings proved a significant relationship between JS, OCS, leadership, EJS, and WE. Equally, [6] examine how good a working environment affects the work performance of teachers across private higher institutions in Buea. The sample size included a total of 107 teachers drawn from 187 teaching staff.…”
Section: Empirical Literaturementioning
confidence: 99%
“…This lead to poor job commitment of some private teachers thereby constantly, increasing their intention to leave their job. Studies have shown that job satisfaction and commitment have a positive impact on organizational performance [5,6]. As such, the satisfaction and commitment of a teacher are considered a significant panacea for their performance [7].…”
Section: Introductionmentioning
confidence: 99%
“…Successful organizations are made by the workers through their performance. The environment is very important in determining the performance of the workers in any field and profession (Lious et al, 2021) and for teachers, it is the classroom instructional environment that they create that also impacts their performance as well as the performance of their students. Education, the process of imparting knowledge, beliefs, religion, norms, and values to the next generation, is a complicated process that requires systematic coordination and cooperation of all the stakeholders; society, teachers, administration, and the students.…”
Section: Introductionmentioning
confidence: 99%